Quest for Female Space in James Joyce’s “Eveline” - Kul Bahadur Rana, (Journal of Development Review, 2025)
James Joyce’s short story “Eveline,” from his collection Dubliners (1914), serves as an insightful exploration of the intersection between gender, space, and paralysis in early twentieth-century Irish society. This paper investigates how Joyce constructs the domestic space as a site of both physical and psychological confinement for the female protagonist, Eveline. Through a close reading of the text, combined with feminist literary theory and spatial critique, the study examines how the story reflects the limited geographies available to women within patriarchal structures. Drawing on theoretical frameworks from Simone de Beauvoir, Michel Foucault, Judith Butler, Henri Lefebvre, Edward Said, and Virginia Woolf, the article argues that Eveline’s hesitation and eventual immobility are not merely individual failures but the result of a deeply internalized spatial and gendered conditioning. The threshold scenes—windows, doorways, the harbor – serve as symbolic representations of Eveline’s liminality and unfulfilled quest for agency. This study contributes to existing Joycean scholarship by foregrounding the spatial politics of gender in “Eveline,” while also offering insights into the broader implications of female mobility and autonomy in colonized and patriarchal societies. By decontextualizing the narrative through spatial and feminist lenses, the paper underscores the necessity of reimagining domesticity and escape as critical to understanding female subjectivity in modernist literature.